Avaliação das Variáveis Meteorológicas e do Manejo sobre a qualidade e produtividade de videiras cultivadas sob base familiar em Pelotas/RS - Radünz, André Luiz (2012)
In order to reach the strengthening and the development of family agriculture as well as the premise of diversification of the productive sources, there appears as an alternative the cultivation of common vineyards destined to the production of home-grown wine, juices and derivatives. Attempts were made to evaluate the existing relationships among local meteorological variables and handling practices, dry pruning and green pruning and the effects on phenological behavior, productive aspects and on the quality of the cultivated grape under the conditions of the region of Pelotas/RS. For this purpose, a family based agricultural property was selected located in the 8TH district of Pelotas/RS, in which the experiment was carried out and where the experimental delineation was composed for a (2 x 2 x 2) factorial, these being: (Bordô and BRS Violeta) cultivar, period of dry pruning (normal and late) and green pruning (with and without defoliation). Evaluations were carried out during harvest of total soluble solids, of the mass of clusters, of the number of clusters of grapes per cluster and production per plant. Moreover, global solar radiation was measured in each treatment, reflected by the canopy and available at the level of clusters as well as the daily temperature of the vineyards, Results demonstrate that the period of dry pruning affected the production and the accumulation of total soluble solids and on cv. BRS Violeta, only the total soluble solids. When relating the period of dry pruning with defoliation over total soluble solids, these differed only in the treatment with defoliation, being greater in the late period. Defoliation carried out on cv. Bordô reduced the number of grapes per cluster. However, it increased weight of the clusters and presented no differences for the BRS Violeta . Defoliation associated with the normal period increased the production per plant and the number of clusters on Bordô and presented no differences on the cv. BRS Violeta. The results demonstration that the average albedo presented short variation 0,287, 0,280, 0,295, 0,297, 0,304 e 0,287 for the respectively treatments BNC, BTC, BTS, VNC, VTC and VTS, being B e V refer of the cultivars Bordô and BRS Violeta, N and T of the dry pruning and C and S with and without. The cv. BRS Violeta presented greater availability of solar radiation at the level of clusters and higher rate of total soluble solids during harvest when compared with cv. Bordô. The period of dry pruning did not represent difference in the quantity of solar radiation available at the level of clusters but the defoliation propitiated increase in incident radiation a the level of clusters for cv. Bordô and BRS Violeta. Solar radiation available at the level of clusters showed itself related to the accumulation of total soluble solids, being greater when the available radiation was greater on cv. Bordô.